Gambusiam affinis (Baird & Girard (Baghdad Science Journal, 2005)
Consists heart mosquito fish amounting to four lounges arranged from back to front and by the path of blood which starts Balab then venous atrium and ventricle and then the arterial bulb. Pocket venous thin wall and contains no barriers muscle and opens to atrium slot sinoatrial Mahrousa Btita LED sinoatrial wall atrium thicker than it is in the pocket venous slightly and characterized its proximity to the barriers muscle short and few in number open atrium to ventricle slot atrioventricular Mahrousa Btita LED fibrillation and ventricular ventricular wall that features a more thicker walls of the corridors of the heart as it contains a spongy layer of muscle barriers many branch opens ventricle to the arterial bulb Balvohh Alhariamillo AlkjrzsoWinnie Skak Ajhaúah highlights Menen inner surface to combine folds longitudinal arrangement has one considers that the bulb arterial is part of the heart, not a blood vessel and that because it is located within the cavity pericardial also the outer layer of the wall surrounded by fabric Dharri squamous simple either the outer layer of blood vessels not surrounded by such a fabric ......